Determinants and Prognostic Value of Longitudinal Strain in Asymptomatic Aortic Stenosis and Preserved Left Ventricular Ejection Fraction—The COFRASA/GENERAC Study. Issue 3 (4th July 2017) - Melissopoulou, Maria; Nguyen, Virginia; Dreyfus, Julien; Attias, David; Tubiana, Sarah; Duval, Xavier; Codogno, Isabelle; Cimadevilla, Claire; Vahanian, Alec; Messika-Zeitoun, David
ABSTRACT: Background: Longitudinal strain has been proposed as a sensitive marker of left ventricular systolic dysfunction. However its prognostic value in patients with aortic stenosis (AS) remains debated. Methods: In a prospective cohort of asymptomatic patients with at least mild, isolated AS and preserved left ventricular ejection fraction (LVEF), clinical, biological measurements, global longitudinal strain (GLS) and basal longitudinal strain (BLS) were performed at study entry. The occurrence of AS-related events (sudden death, congestive heart failure, new onset of symptoms) or aortic valve replacement within two years was recorded prospectively. Results: A total of 140 patients were enrolled and 21 events occurred. In contrast to GLS, BLS was significantly correlated to AS severity ( p  = 0.0006 with PV, p  = 0.0002 with MPG, p  = 0.01 with AVA, and p  = 0.0009 with AVAi) and predicted the occurrence of AS-related events in the subset of severe AS in univariate analysis ( p  = 0.03) and after adjustment for AVA ( p  = 0.01), AVAi ( p  = 0.01), PV ( p  = 0.045), and MPG ( p  = 0.05). However, there was an important overlap of baseline BLS values between patients who developed symptoms and those who did not and repeated BLS measurements showed no difference between baseline values and those obtained at the time of overt symptoms in nine patients ( p  = 0.38). Conclusion: BLS was statistically predictive of AS-related events in the subset of severe AS. However, overlap of BLS values between groups of symptomatic status and similar values at baseline and at the time of overt symptoms raise the question of its use at an individual level at least as a single isolated parameter.